The Effect of Quantum Teaching Learning Model on the Physics Learning Outcomes of Class X SMK Negeri 3 Lubuklinggau - Wita Romita Ayu; Tri Ariani; Wahyu Arini (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2019)
The purpose of this study was to determine